2017
DOI: 10.1080/17429145.2017.1308569
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping influences component and content change of flavonoids in root exudates and nodulation of Faba bean

Abstract: Flavonoids produced by legume roots are signal molecules acting as nod gene inducers for the symbiotic rhizobium partner. Nevertheless, the changes of flavonoids in root exudates in intercropping system are still unknown. Based on pot experiment of faba bean and wheat intercropping, here we showed that faba bean and wheat intercropping increased the nodules number and dry weight, dry weight per nodule of faba bean compared with those found in monocropping, and the increase of faba bean nodulation was likely ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Faba bean intercropped with garlic obviously up-regulated the nodule numbers and nodules dry www.nature.com/scientificreports www.nature.com/scientificreports/ weight of faba bean 27 . Likewise, in the intercropping system of wheat and broad bean, the intercropped faba bean could up-regulate the nodule numbers, nodules dry weight and single nodule dry weight, suggesting that the intercropping could enhance the nodulation ability of faba bean 16 . The mentioned results may support that intercropping between alfalfa and triticale can enhance alfalfa's ability to compete for nitrogen, and the nodulation and N fixation ability of alfalfa are derived from low N. In this regard, the closer the intercropped roots of alfalfa and triticale interact, the better the nodulation and N fixation in alfalfa will exhibit.…”
Section: Root Interaction Promotes Nodulation and N Fixation Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Faba bean intercropped with garlic obviously up-regulated the nodule numbers and nodules dry www.nature.com/scientificreports www.nature.com/scientificreports/ weight of faba bean 27 . Likewise, in the intercropping system of wheat and broad bean, the intercropped faba bean could up-regulate the nodule numbers, nodules dry weight and single nodule dry weight, suggesting that the intercropping could enhance the nodulation ability of faba bean 16 . The mentioned results may support that intercropping between alfalfa and triticale can enhance alfalfa's ability to compete for nitrogen, and the nodulation and N fixation ability of alfalfa are derived from low N. In this regard, the closer the intercropped roots of alfalfa and triticale interact, the better the nodulation and N fixation in alfalfa will exhibit.…”
Section: Root Interaction Promotes Nodulation and N Fixation Abilitymentioning
confidence: 99%
“…The N content in the soil is down-regulated, would induce inducing the diffusion of O 2 in the nodule cortex, up-regulating the respiration rate of nodule and enhancing the nitrogenase activity 15 . Moreover, cereal/legume intercropping can induce the roots of cereal to secrete flavonoids to form nodules 16 . Banik and Sharma 17 reported that intercropping of baby maize and legumes enhanced the ability of legume nodulation.…”
mentioning
confidence: 99%
“…The accumulation of autotoxic compounds is an important factor contributing to soil sickness, as autotoxic compounds can promote the propagation of soil-borne pathogens (Bever et al, 2012;Zhou et al, 2017). It has been shown that interspecific plant interactions are able to change plant secondary metabolism (Broz et al, 2010;Li et al, 2016;Liu et al, 2017). Lv et al (2018) found that the intercropping of wheat inhibited watermelon from exudating phenolic autotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids serve as primary signals and are released by the host plants that act as chemoattractants [ 42 ], activating the expression of rhizobia node genes. The function of flavonoids in the nodulation process has been studied by several researchers [ 42 - 44 ]. Van Noorden et al [ 45 ] observed the interaction of Sinorhizobium meliloti with 131 identified proteins in Medicago truncatula .…”
Section: Plant-microbe Beneficial Interactionmentioning
confidence: 99%